PHENOTYPIC PERFORMANCE AND GRAIN YIELD OF COMPOSITE MAIZE (Zea mays) LINE IN WEST JAVA - Irma Noviana; Tri Hastini; Iskandar Ishaq (Widyariset, 2012)
Phenotypic performance and yields needed for specific lines selection. Experiment was conducted to determine phenotypic performance and grain yield of nine promising lines of composite maize (Zea mays) as the information needed to released as specific varieties of West Java. A set of field experiment were established in Majalengka and Sumedang district, from April to Juli 2010. Nine maize lines and 3 control varieties i.e. Gumarang, Makmur-1, and Sinta-1 were planted based on a randomized block design. The result showed that AS-1 has better ear performance than control varieties. R2, R3, and AS-1 has a character of high yields potential equivalent to the varieties and opportunity to be released as specific composite maize varieties of West Java.